A New Pharmacokinetic Model Describing the Biodistribution of Intravenously and Intratumorally Administered Superparamagnetic Iron Oxide Nanoparticles (SPIONs) in a GL261 Xenograft Glioblastoma Model - Klapproth AP (Dove Medical Press, 2020)
Alexander P Klapproth,1,2,* Maxim Shevtsov,1,3– 7,* Stefan Stangl,1 Wei Bo Li,2 Gabriele Multhoff1 1Center for Translational Cancer Research Technische Universität München (TranslaTUM), Klinikum Rechts Der Isar, Munich, Germany; 2Institute of Radiation Medicine, Helmholtz Zentrum München, German Research Center for Environmental Health (GmbH), Munich, Germany; 3Institute of Cytology of the Russian Academy of Sciences (RAS), St. Petersburg, Russia; 4Department of Biotechnology, First Pavlov State Medical University of St. Petersburg, St. Petersburg, Russia; 5Almazov National Medical Research Centre, Russian Polenov Neurosurgical Institute, St. Petersburg, Russia; 6National Center for Neurosurgery, Nur-Sultan, Kazakhstan; 7Department of Biomedical Cell Technologies, Far Eastern Federal University, Vladivostok, Russia*These authors contributed equally to this workCorrespondence: Maxim Shevtsov; Wei Bo Li Email maxim.shevtsov@tum.de; wli@helmholtz-muenchen.deBackground: Superparamagnetic iron oxide nanoparticles (SPIONs) have displayed multifunctional applications in cancer theranostics following systemic delivery. In an effort to increase the therapeutic potential of local therapies (including focal hyperthermia), nanoparticles can also be administered intratumorally. Therefore, the development of a reliable pharmacokinetic model for the prediction of nanoparticle distribution for both clinically relevant routes of delivery is of high importance.Materials and Methods: The biodistribution of SPIONs (of two different sizes – 130 nm and 60 nm) radiolabeled with zirconium-89 or technetium-99m following intratumoral or intravenous injection was investigated in C57/Bl6 mice bearing subcutaneous GL261 glioblastomas. Based on PET/CT biodistribution data, a novel pharmacokinetic model was established for a better understanding of the pharmacokinetics of the SPIONs after both administration routes.Results: The PET image analysis of the nanoparticles (confirmed by histology) demonstrated the presence of radiolabeled nanoparticles within the glioma site (with low amounts in the liver and spleen) at all investigated time points following intratumoral injection. The mathematical model confirmed the dynamic nanoparticle redistribution in the organism over a period of 72 h with an equilibrium reached after 100 h. Intravenous injection of nanoparticles demonstrated a different distribution pattern with a rapid particle retention in all organs (particularly in liver and spleen) and a subsequent slow release rate.Conclusion: The mathematical model demonstrated good agreement with experimental data derived from tumor mouse models suggesting the value of this tool to predict the real-time pharmacokinetic features of SPIONs in vivo. In the future, it is planned to adapt our model to other nanoparticle formulations to more precisely describe their biodistribution in in vivo model systems.Keywords: mathematical modeling, SPIONs, superparamagnetic iron oxide nanoparticles, pharmacokinetic model, glioblastoma, biodistribution